2023
DOI: 10.3390/ma16062533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Characteristics of TiO2 Coatings on the Response of Gingival Cells: A Systematic Review of In Vitro Studies

Abstract: The soft tissue-implant interface requires the formation of epithelium and connective tissue seal to hinder microbial infiltration and prevent epithelial down growth. Nanoporous titanium dioxide (TiO2) surface coatings have shown good potential for promoting soft tissue attachment to implant surfaces. However, the impact of their surface properties on the biological response of gingival cells needs further investigation. This systematic review aimed to investigate the cellular behavior of gingival cells on TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The higher wettability, which represents the hydrophilic behavior of the nanostructure TiO 2 surface, promoted protein adsorption, encouraged cell adhesion and proliferation, and consequently enhanced connective tissue regeneration [ 29 , 30 ]. Furthermore, the author's previous in vitro review has shown that TiO 2 coatings with smooth surface topography and good wettability promote fibroblast and epithelial cell response compared with machined surfaces [ 31 ]. However, the outcomes of the present systematic review did not consistently align with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher wettability, which represents the hydrophilic behavior of the nanostructure TiO 2 surface, promoted protein adsorption, encouraged cell adhesion and proliferation, and consequently enhanced connective tissue regeneration [ 29 , 30 ]. Furthermore, the author's previous in vitro review has shown that TiO 2 coatings with smooth surface topography and good wettability promote fibroblast and epithelial cell response compared with machined surfaces [ 31 ]. However, the outcomes of the present systematic review did not consistently align with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have demonstrated that nanoporous TiO 2 coatings enhanced gingival cell response [ 5 , 21 , 29 , 30 ]. It has been shown that nanostructured TiO 2 coatings with smooth surface topography and good wettability promote favorable fibroblast and epithelial cell responses compared to machined surfaces which ultimately affects the rate and quality of new tissue formation [ 31 ]. However, in vitro studies cannot truly represent the biological process of oral implant and abutment integration.…”
Section: Introductionmentioning
confidence: 99%